Folate-receptor 1 level in periodontal disease: a pilot study - Duygu Alkan; Berrak Guven; Cigdem Coskun Turer; Umut Balli; Murat Can (BMC, 2019)
Abstract Background The purpose of this study was to investigate gingival crevicular fluid (GCF) and serum folate-receptor 1 (FOLR1) levels in subjects with different periodontal status. Methods The study consists of three groups: Healthy group (n = 15), gingivitis group (n = 15) and chronic periodontitis group (n = 15). Clinical periodontal parameters including probing pocket depth (PPD), clinical attachment level (CAL), gingival index (GI) and bleeding on probing (BOP) were assessed. GCF and serum samples were collected from each patient and were analyzed FOLR1 levels by enzyme-linked immunosorbent assay. Results The values of FOLR1 in GCF were higher in gingivitis and periodontitis groups than among patient in control group (p < 0.016). Serum FOLR1 levels showed no significant difference between the groups. A significant correlation was observed between FOLR1 levels of GCF and BOP (p < 0.05). Conclusions Our preliminary data suggest that FOLR1 is not useful in monitoring the periodontal disease. Further studies are necessary to clarify the role, regulation and function of folate and it's receptors in the pathogenesis of periodontal disease.